Analysis of postmortem metabolic changes in rat kidney cortex using Fourier transform infrared spectroscopy. Issue 1 (2008) - Huang Huang, Ping Ping; Ke Ke, Yong Yong; Lu Lu, Qinyang Qinyang; Xin Xin, Bo Bo; Fan Fan, Shuanliang Shuanliang; Yang Yang, Guangde Guangde; Wang Wang, Zhenyuan Zhenyuan
Abstract : Estimation of the time since death (postmortem interval, PMI) is one of the most difficult problems in forensic investigations and many methods currently are utilized to estimate the PMI. The aim of this study was to investigate the changes of Fourier transform infrared (FT-IR) spectra of rat kidney cortex from time zero to 168 h postmortem at molecular level. The spectra of rat kidney cortex displayed the prominent changes with increasing postmortem interval. (1) Significant increase in the intensity of the C–H stretching bands at 2958, 2925, 2871, 2852 cm –1, the ═C–H stretching band at 3012 cm –1, the CO2 – symmetric stretching band at 1396 cm –1 and the N–H bend, C–N stretching at 1541 cm –1 ; (2) significant decrease in the intensity of the PO2 – stretching band at 1238, 1080 cm –1 ; (3) the intensity of at 3303, 1652 and 1170 cm –1 remained relatively stable. The linear regression analysis of the various absorption intensity and area ratios against the PMI shows a close correlation, maximum for A 1541 / A 1396 ratio ( R 2 ═ 0.95) and minimum for I 1080 / I 1396 ratio ( R 2 ═ 0.70). Our results indicate that FT-IR spectroscopy may be a useful technique for estimating the short- and long-term PMI.